Tailoring Re-loaded core–shell Ni structures embedded in mesoporous silica for the selective transformation of levulinic acid into γ-valerolactone - Yupawan Maneewong; Pratikkumar Lakhani; Sakhon Ratchahat; Chularat Sakdaronnarong; Wanwisa Limphirat; Suttichai Assabumrungrat; Kittisak Choojun; Tawan Sooknoi; Keiichi Tomishige; Atthapon Srifa (Journal of Materials Chemistry A, 2026)
A Re-doped Ni@mSiO 2 core–shell catalyst with uniform metal dispersion enables the efficient and sustainable hydrogenation of levulinic acid to γ-valerolactone, showing high activity, selectivity, and reusability for sustainable biomass valorization.
Keywords: Catalysis for Biomass Conversion; Mesoporous Materials and Catalysis; Layered Double Hydroxides Synthesis and Applications